2012
DOI: 10.1111/j.1399-3054.2012.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of winter icing events on the growth, phenology and physiology of sub‐arctic dwarf shrubs

Abstract: The Arctic is experiencing the greatest climate change in winter, including increases in freeze-thaw cycles that can result in ice encasement of vegetation. Ice encasement can expose plants to hypoxia and greater temperature extremes, but currently the impacts of icing on plants in the field remain little understood. With this in mind, a unique field manipulation experiment was established in heathland in northern Sweden with ice encasement simulated in early March 2008, 2009 and 2010 until natural thaw each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 71 publications
8
40
0
Order By: Relevance
“…Overall, this study supports the intermediate to high tolerance of icing observed recently in a shorter duration icing study (Preece et al . ), but further shows that this level of tolerance is not lost even under ice encasement of much longer duration, as in the case of the January icing here.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Overall, this study supports the intermediate to high tolerance of icing observed recently in a shorter duration icing study (Preece et al . ), but further shows that this level of tolerance is not lost even under ice encasement of much longer duration, as in the case of the January icing here.…”
Section: Discussionsupporting
confidence: 57%
“…It was expected that ice encasement would decrease growth of the three dwarf shrubs, although possibly only following the January icing, given the tolerance to shorter duration icing shown previously (Preece et al . ). However, there were no effects of icing on apical growth of any species, indicating that the plants are able to tolerate the ice encasement – including the much longer ice encasement duration of the January icing – with no negative impacts on shoot extension.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar population crashes to semidomesticated reindeer caused by ground ice are also known from other northern regions and years (Riseth et al 2011;Vikhamar-Schuler et al 2013;Rasmus et al 2016). Ground ice has a negative impact on vegetation encased in ice (Gudleifsson 2009;Bjerke et al 2011;Preece et al 2012). The winter of 2012 also led to negative plant responses, similar to those recorded after the 2006 winter (Bjerke et al 2014).…”
Section: B Winter Warming Trends In the Twenty-first Centurysupporting
confidence: 58%
“…2a), but we choose to use a consistent season duration to facilitate climate comparisons across all stations. Plant species under the snow cover have been observed to respond differently to extraordinary warming events, depending on the timing of their occurrence during the winter season (Bokhorst et al 2010Preece and Phoenix 2014). Therefore, we also consider three subperiods: 1) early winter (OctoberNovember), 2) midwinter (December-February), and 3) late winter (March-April).…”
Section: Introductionmentioning
confidence: 99%